HUBUNGAN TINGKAT PENDIDIKAN DAN PENGETAHUAN TENTANG STATUS GIZI DENGAN ANGKA KEJADIAN STUNTING DI DESA SECANGGANG KABUPATEN LANGKAT - SUCI MARDIANA; ANDRI YUNAFRI (LP2MTBM MAKARIOZ, 2021)
Stunting is a condition of growth disturbance in children namely the child's height is lower or shorter (dwarf) than his agestandard, as a result of the low nutritional and health status in the pre and post-natal period. The level of education andknowledge of the mother greatly influences the level of the mother's ability to manage family resources, in order to obtainsufficient food needed. To determine the relationship between education level and knowledge about nutritional status withthe incidence of stunting in Secanggang Village, Langkat Regency. This type of research is analytic descriptive research withcross-sectional research design. Subjects in this study were mothers who have children aged 0-59 months with stuntingcondition who reside in Secanggang District, Langkat Regency as many as 27 people. The results showed there was arelationship between the level of education and knowledge about nutritional status with the incidence of stunting inSecanggang Village, Langkat Regency.